2008
DOI: 10.1016/j.neuron.2007.12.028
|View full text |Cite
|
Sign up to set email alerts
|

Satb2 Is a Postmitotic Determinant for Upper-Layer Neuron Specification in the Neocortex

Abstract: Pyramidal neurons of the neocortex can be subdivided into two major groups: deep- (DL) and upper-layer (UL) neurons. Here we report that the expression of the AT-rich DNA-binding protein Satb2 defines two subclasses of UL neurons: UL1 (Satb2 positive) and UL2 (Satb2 negative). In the absence of Satb2, UL1 neurons lose their identity and activate DL- and UL2-specific genetic programs. UL1 neurons in Satb2 mutants fail to migrate to superficial layers and do not contribute to the corpus callosum but to the corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
747
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 616 publications
(795 citation statements)
references
References 36 publications
45
747
3
Order By: Relevance
“…indicating that precise levels of CSMN-specific genes are a fundamental requisite for correct differentiation of corticofugal neurons. Finally, because COUP-TFI and Fezf2 are both expressed in postmitotic neurons, it is possible that abnormal differentiation of CSMN and corticothalamic neurons in the absence of COUP-TFI occurs at a postmitotic level, as recently shown for other cortical transcriptional regulators (8,30,31,32).…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentmentioning
confidence: 84%
“…indicating that precise levels of CSMN-specific genes are a fundamental requisite for correct differentiation of corticofugal neurons. Finally, because COUP-TFI and Fezf2 are both expressed in postmitotic neurons, it is possible that abnormal differentiation of CSMN and corticothalamic neurons in the absence of COUP-TFI occurs at a postmitotic level, as recently shown for other cortical transcriptional regulators (8,30,31,32).…”
Section: Coup-tfi Is a Negative Regulator Of A Genetic Csmn Differentmentioning
confidence: 84%
“…Notable among the genes significantly up-regulated at E12.5 in the Ezh2-null cortex are a large set of transcription factors and other genes specifically expressed in differentiating cortical neurons (Fig. 2C), such as Neurod6, Mef2c, Myt1l, and Bcl11b (expressed in all cortical neurons) and genes specifically expressed in either early-born or later-born cortical neuron types, including corticothalamic and callosal projection neurons (25): Reelin (marginal zone neurons); Moxd1 and Tmem163 (subplate neurons); Tbr1 and Foxp2 (layer 6 neurons), Foxo1 and Pou3f1/ SCIP (layer 5 neurons); Lmo4 and Foxp1 (callosal projection neurons of layers 3-5); Bhlhb5/Bhlhe22 (neurons in layers 2-5); Ror-beta (layer 4 neurons); and Satb2 (neurons in layers 2-4) (25)(26)(27)(28)(29)(30)(31). The increase in layer-specific neuronal gene expression at this early point in cortical development suggested that cortical development may be more advanced in the Ezh2-null cortex than in control littermates.…”
Section: Loss Of Prc2 Function Results In Up-regulated Gene Expressiomentioning
confidence: 99%
“…Pyramidal neurons can be subdivided into numerous subtypes, defined in vivo by a repertoire of molecular markers, identifying distinct layer-specific neuronal populations 7,[22][23][24] . To examine the diversity of the neuronal repertoire derived from ESCs in DDM plus cyclopamine, we studied the expression of a large set of layer-specific markers corresponding to the major subtypes of cortical neurons generated in vivo in the mouse (Fig.…”
Section: Sequential Cortical Neurogenesis From Escsmentioning
confidence: 99%